Genetic Diversity Among Oil Palm Parental Genotypes Revealed by Microsatellite Polymorphism and its Relationship to Progeny Performance - Abdullah, Norziha (2008)
Oil palm (Elaeis guineensis Jacq.) is a perennial crop. One complete cycle of selection takes about 10 to 15 years and due to that, breeding and selection of the crop is slow. By developing marker assisted selection for this species, the time needed for breeding and selection could be decreased to almost half compared to that through conventional method. This study involves investigating the genetic relationship between the parental palms (dura and pisifera) and their progenies based on microsatellite markers. The general objectives of this study are to estimate genetic diversity between Dura and Pisifera parental combinations using microsatellite markers and to investigate the association between genetic diversity and progeny performance. Nine microsatellite markers were used to screen selected parental palms (15 parental duras and 4 parental pisiferas) and their progenies (16 DxP crosses). Data were scored and analysed using Biosys-1 software to calculate the genetic distance values and subsequently constructing the dendrogram. A total of 29 polymorphic bands were generated. The genetic distances among progenies ranged from 0.444 to 0.746. Considerable polymorphism of 94.5% was observed in DxP progenies. Cluster analysis based on genetic distances revealed associations among progenies which were closely in agreement with the pedigree data. The performance of 16 Dura x Pisifera progenies was evaluated for quantitative characters. A large variation among the genotypes was detected in these DxP progenies for yield and yield components. Based on pisifera components, shell to fruit ratio (S/F) exhibited the highest heritability (58.18%) among the traits examined whereas for duras within pisifera, the highest heritability correspond to palm height (HT) and rachis length (RL). Correlation analyses between genetic distances and progeny performance were estimated by simple correlation coefficient. The correlation values of genetic distances with progeny performance were mostly non-significant, except for mean nut weight (MNW) and leaf number (LN). However, the correlation of genetic distances with these characters is too low to be used as predictive value. These results indicate that genetic distances based on the microsatellite markers used in this study may not be useful for predicting progeny performance in oil palm.